Predatory Pricing in Indonesia’s Digital Trade Ecosystem: An Analysis of Inhibiting Factors and the Ideal Model for Equitable Regulation: Predatory Pricing dalam Ekosistem Perdagangan Digital di Indonesia: Analisis Faktor Penghambat dan Model Ideal Pengaturan yang Berkeadilan - Adam, Richard C.; Leeland, Deryl (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Indonesia’s rapidly expanding digital trade ecosystem has transformed market structures and intensified competition. Specific background: Within this environment, predatory pricing as a strategy of selling goods or services below cost to weaken competitors has become increasingly difficult to regulate due to digital platforms’ unique cost structures, cross-subsidization, and algorithmic pricing. Knowledge gap: Indonesian competition law lacks clear benchmarks for determining below-cost pricing, exclusionary intent, and recoupment, creating uncertainty in enforcement, especially against foreign digital actors. Aims: This study analyzes normative and practical barriers to enforcing predatory pricing rules in e-commerce and proposes an equitable regulatory model. Results: The findings show unclear cost definitions, limited data transparency, dynamic promotional practices, jurisdictional constraints, and the absence of technical guidelines, all of which impede consistent legal assessment. Novelty: This research offers a multidimensional regulatory framework informed by comparative practices from the United States, European Union, and China, incorporating algorithmic transparency, structural market effects, and temporal indicators of exclusion. Implications: A more adaptive and comprehensive regulatory structure is needed to strengthen legal certainty, protect SMEs, prevent digital-market exclusion, and promote a fair and sustainable competitive environment in Indonesia’s digital economy. Highlights: The study exposes major gaps in Indonesia’s legal standards for identifying below-cost pricing in digital markets. Enforcement is hindered by limited data access, dynamic promotional models, and cross-border platform operations. A new multidimensional regulatory model is proposed to ensure fairness, SME protection, and sustainable digital competition. Keywords: Predatory Pricing, Digital Trade, Competition Law, E-Commerce Regulation, Legal Certainty